Photochemical origin of SiC2 in the circumstellar envelope of carbon-rich AGB stars revealed by ALMA - Feng, Yanan; Li, Xiaohu; Millar, Tom J.; Szczerba, Ryszard; Wang, Ke; Quan, Donghui; Qin, Shengli; Fang, Xuan; Tuo, Juan; Miao, Zhenzhen; Ma, Rong; Xu, Fengwei; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Whether SiC2 is a parent species, that is formed in the photosphere or as a by-product of high-temperature dust formation, or a daughter species, formed in a chemistry driven by the photodestruction of parent species in the outer envelope, has been debated for a long time. Here, we analyze the ALMA observations of four SiC2 transitions in the CSEs of three C-rich AGB stars (AI Vol, II Lup, and RAFGL 4211), and found that SiC2 exhibits an annular, shell-like distribution in these targets, suggesting that SiC2 can be a daughter species in the CSEs of carbon-rich AGB stars. The results can provide important references for future chemical models.